Peran Kewirausahaan dalam Pembangunan Ekonomi - Ahmad Fajri (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2021)
ABSTRACT This article discusses the role of entrepreneurship in economic development. This article reviews the relationship and role of entrepreneurship in economic development in a country, and how entrepreneurship can contribute to gross domestic product (GDP). And how is the relationship between entrepreneurship and job creation. The results of the discussion in this article; entrepreneurship is the heart of economic development, entrepreneurship is an innovator that creates jobs and in the end people's incomes increase which can affect gross domestic product (GDP). However, only productive entrepreneurship and supported by a good ecosystem can support economic growth. Keywords; The Role of Entrepreneurship, Labor, Economic Development ABSTRAK Artikel ini mendiskusikan tentang peran kewirausahaan dalam pembangunan ekonomi. Artikel ini mengulas bagaimana hubungan dan peran kewirausahaan dalam pembangunan ekonomi disebuah negara, serta bagaimana kewirausahaan dapat berkontribusi pada produk domistik bruto (PDB). Dan bagaimana hubungan kewirausahaan dengan penciptaan lapangan kerja. Hasil diskusi pada artikel ini; kewirausahaan merupakan jantung pembangunan ekonomi, kewirausahaan merupakan inovator pencipta lapangan kerja dan pada akhirnya pendapatan masyarakat meningkat yang dapat mempengaruhi produk domistik bruto (PDB). Namun, hanya kewirausahaan yang produktif dan didukung ekosistem yang baik dapat menunjang pertumbuhan ekonomi. Kata Kunci; Peran Kewirausahaan, Tenaga Kerja, Pembangunan Ekonomi